A Comparison by Milk Feeding Method of the Nutrient Intake of a Cohort of Australian Toddlers - Scott, Jane; Davey, K.; Ahwong, E.; Devenish, G.; Diep, H.; Do, L. (MDPI Publishing, 2016)
Breastfeeding is recommended beyond 12 months of age, but little is known about the contribution of breastmilk and infant formula to the nutritional intake of toddlers as they transition to a family diet in the second year of life. This study is a cross-sectional analysis of data collected from a birth cohort study in Adelaide, Australia. Dietary intake data were collected when children were approximately 1 year of age by an interviewer-administered multi-pass 24 h recall and a mother-completed 2 days food diary. Children were categorized according to their milk feeding method, i.e., breastmilk, infant formula, combination or other, and their nutrient intakes compared with recommended nutrient reference values. Complete data were available for 832 children, of which 714 had plausible energy intakes. Breastmilk and formula made a substantial contribution to the nutrient intake of those toddlers, contributing 28% and 34% of total energy, and 16% and 26% of protein intake, respectively when not drunk in combination. In general, Australian toddlers transitioning to the family diet consumed nutritionally adequate diets, although almost one quarter of all children and half of breastfed children with plausible intakes had iron intakes below the estimated average requirement, placing them at risk of iron deficiency.